2003
DOI: 10.1161/01.hyp.0000051889.62249.5d
|View full text |Cite
|
Sign up to set email alerts
|

GTP Cyclohydrolase 1 Downregulation Contributes to Glucocorticoid Hypertension in Rats

Abstract: Abstract-NO, a potent vasodilator, has been implicated in the pathogenesis of glucocorticoid hypertension. NO synthase requires the cofactor tetrahydrobiopterin for the production of NO. Guanosine-triphosphate (GTP) cyclohydrolase 1 is the rate-limiting enzyme for the production of tetrahydrobiopterin, and in the presence of low levels of tetrahydrobiopterin, NO production is decreased. We have previously shown that tetrahydrobiopterin-dependent vasodilation is impaired in rats with glucocorticoid hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Both cyclic adenosine monophosphatedependent protein kinase and stress-activated protein kinases are able to activate GTP cyclohydrolase gene transcription in normal conditions. 37 By contrast, glucocorticoids decrease GTPCH gene transcription, 38,39 and transforming growth factor beta (TGF-␤) has been shown to counterbalance the cytokine activation of nitric oxide synthase in endothelial cells by down-regulating GTPCH mRNA expression. [40][41][42] Because increased levels of TGF-␤ are present in cirrhosis, speculating that TGF-␤ could play a role in the decreased GTPCH expression found in cirrhosis is tempting.…”
Section: Discussionmentioning
confidence: 99%
“…Both cyclic adenosine monophosphatedependent protein kinase and stress-activated protein kinases are able to activate GTP cyclohydrolase gene transcription in normal conditions. 37 By contrast, glucocorticoids decrease GTPCH gene transcription, 38,39 and transforming growth factor beta (TGF-␤) has been shown to counterbalance the cytokine activation of nitric oxide synthase in endothelial cells by down-regulating GTPCH mRNA expression. [40][41][42] Because increased levels of TGF-␤ are present in cirrhosis, speculating that TGF-␤ could play a role in the decreased GTPCH expression found in cirrhosis is tempting.…”
Section: Discussionmentioning
confidence: 99%
“…First, the increased levels of vascular superoxide anions in hypertension might directly inactivate NO. 35,36 Second, the improvement of endothelium-dependent NO-mediated response by the addition of synthetic tetrahydrobiopterin, or its intermediate donor sepiapterin, to vessel rings from animals with hypertension 3,4 suggests that diminished levels of this eNOS cofactor may contribute to the endothelial dysfunction related to NO deficiency. Third, the downregulation of eNOS expression in the coronary arterioles from hypertensive animals, as revealed by immunohistochemistry herein, is another potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a markedly reduced endothelium-dependent vasodilation in both large and small coronary arteries from hypertensive humans and animal models of hypertension. 1 Mounting evidence suggests that this vascular impairment may be related to a diminished production and bioavailability of the potent vasodilator nitric oxide (NO), which may result from an increased vascular production of superoxide anion 2 or decreased endothelial levels of tetrahydrobiopterin 3,4 or L-arginine. 5 Interestingly, administration of NO precursor L-arginine restores endothelium-mediated vasodilatory function in patients with essential hypertension, 5 improves coronary hemodynamics in spontaneously hypertensive rats, 6 and increases NO production and reduces blood pressure in hypertensive rats with 7 or without 8 renal failure.…”
mentioning
confidence: 99%
“…27,28 In a glucocorticoid-induced rat model of hypertension, GTPCH mRNA levels were reduced, and impaired endotheliumdependent relaxations could be restored by incubating vessels in sepiapterin, which suggests reduced BH4 bioavailability as a cause of eNOS uncoupling. 89 However, it was not determined whether these abnormalities were a direct effect of glucocorticoid treatment or secondary to the experimental hypertension, and the relevance of these findings to human vascular disease remains uncertain. More recent studies in the DOCA-salt hypertensive mouse also found that decreased BH4 levels were related to reduced GTPCH activity; supplementation of BH4 or increased BH4 synthesis by adenoviral gene delivery of GTPCH restored BH4 levels and normalized eNOS function.…”
Section: Reduced Bh4 Synthesismentioning
confidence: 99%